Peningkatan Kesadaran Masyarakat Menghadapi Pandemi Covid-19 di Desa sukawati, Kabupaten Gianyar, Bali - I Made Artika; Cok Istri Agung T Apriliyanti; Sang Ayu Putu Didi K Agustini; Ni Putu Asri Ratna Suhita; Ni Putu Peggy Liliyani; Sang Ayu Made Sri Tandewi; Ni Kadek Sintya Anggreni; I Nyoman Rai Widiartha Kesuma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
Sukawati Village is one of the tourist villages located in Sukawati, Gianyar, Bali. Sukawati Village has the potential that can be developed optimally if the role of the community, Sukawati Village officials, village youths, and farmer groups can unite in carrying out and developing the existing potential. Before the KKN-T program which was carried out in Sukawati Village, several problems had not been resolved by the village and the community, such as the minimal publications regarding Sukawati Village, limitations in marketing and financial strategies, and the existence of the Covid-19 pandemic which was the biggest problem. hampers economic and tourism activities. The activities carried out during the KKN-T in Sukawati Village are based on the main problems faced. The activities carried out received appreciation and support from village officials, the community, and village youth. The activities carried out produce each output based on the intended target. Activities carried out are more focused on community empowerment, such as the implementation of training in the fields of economy, technology, and health. Activities in the health sector include training in making soap and hand sanitizers as a means of dealing with the Covid-19 pandemic situation. For the economic sector, namely the socialization of financial strategies and marketing strategies. Activities in the field of technology include training village officials in creating village websites. The results obtained from this activity are in the form of increased sensitivity to the environment and surrounding communities, caring for each other, helping each other to help advance Sukawati Village during the pandemic and post-Covid-19 pandemic. We pack the training provided and make it in the form of a learning video so that in the future it can be used as a reference by the community and can be accessed on YouTube, Whatsapp groups, and Facebook in Sukawati Village. Keywords: Sukawati Village, liquid soap, hand sanitizer, website, marketing, covid-19